Comparative in-vitro quality assessment of Risperidone Tablets marketed in Kaduna State, Nigeria. - Oloyede, Rukayyat Bukola; Musa, Aminu; Mustapha, Lukman; Poyi, Olanike Catherine (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Approximately 1% of the world population develops psychosis during their lifetime. Risperidone, a benzisoxazole derivative, has been found to be effective in the management of psychosis especially in refractory psychotic patients with minimal side effects. This has contributed to its widespread use, resulting in the emergence of numerous generic brands. A comparative in-vitro quality assessment was carried out on four generic brands (A, B, C and D) and the innovator brand (E) of 2 mg risperidone tablets. Tests on uniformity of weight, friability, disintegration, dissolution and assay were carried out on the five brands and the result of the generics was compared with that of the innovator. The innovator brand passed all the tests. The generic brands passed the uniformity of weight, friability and disintegration tests, not exceeding the acceptable limits (BP, 2009). Only brand A failed the assay with a percentage content of 46 %. Brands C and D were found to have dissolution differencefactors within the accepted range of 0-10 %, but their similarity factors fell outside the acceptable range of 50-100 %. Brands A and B failed the dissolution tests entirely. This suggests that some of the generics of risperidone tablets marketed in Kaduna fall below the acceptable specifications.